Attenuation of CD47-SIRPα Signal in Cholangiocarcinoma Potentiates Tumor-Associated Macrophage-Mediated Phagocytosis and Suppresses Intrahepatic Metastasis - Kulthida Vaeteewoottacharn; Ryusho Kariya; Phattarin Pothipan; Sawako Fujikawa; Chawalit Pairojkul; Sakda Waraasawapati; Kazuhiko Kuwahara; Chaisiri Wongkham; Sopit Wongkham; Seiji Okada (Translational Oncology, 2019)
The involvement of chronic inflammation in cholangiocarcinoma (CCA) progression is well established. Cluster of differentiation 47 (CD47) is mutually expressed in various cancers and serves as a protective signal for phagocytic elimination. CD47 signaling blockage is a recent treatment strategy; however, little is known regarding CD47 in CCA. Therefore, the potential use of CD47 targeting in CCA was focused. CD47 was highly expressed in CCA compared to hepatocellular carcinoma (HCC). Disturbance of CD47-signal regulatory protein-α (SIRPα) interaction by blocking antibodies promoted the macrophage phagocytosis. The therapeutic potential of anti-CD47 therapy was demonstrated in liver metastatic model; alleviation of cancer colonization together with dense macrophage infiltrations was observed. The usefulness of anti-CD47 was emphasized by its universal facilitating macrophage activities. Moreover, increased production of inflammatory cytokines, such as IL-6 and IL-10, in macrophage exposed to CCA-conditioned media suggested that CCA alters macrophages toward cancer promotion. Taken together, interfering of CD47-SIRPα interaction promotes macrophage phagocytosis in all macrophage subtypes and consequently suppresses CCA growth and metastasis. The unique overexpression of CD47 in CCA but not HCC offers an exceptional opportunity for a targeted therapy. CD47 is therefore a novel target for CCA treatment.